Behind the boardroom's door: the role and contribution of corporate boards - Simões, A. (2013)
So far, academicians have not been able to empirically confirm that boardroom reforms will lead to more effective boards and ultimately positively affect corporate performance. As social actors we all have biased views, as do boardroom members, thus it is necessary to analyse directors’ perceptions about their role in order to understand if they are aligned and acting accordingly. The research goal is then to understand what is, in fact, directors’ role and contribution. Through a survey-based method board members from Portuguese listed firms were requested to rate the Chairman, the Board, the Senior Independent Director and the CEO performance, through their own perceptions. The survey draws three key conclusions: first, there are, generally, many inconsistencies around the board role boundaries between the chairman and the CEO and, particularly, around their strategic involvement. Second, tensions arise from the way this relationship evolves affecting both teams (the executive and non-executive directors) and third, there is an absence of a clear picture of the board’s role regarding its strategic involvement. This study, whilst exploring and understanding directors and their interactions inside the boardroom in a non-Anglo-American context, contributes to opening the ‘black-box’ of board dynamics, thus ‘dismantling the fortress’ in boards studies.